KINERJA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) DALAM PENYEDIAAN DATA (Studi Kasus Penyelesaian Sangketa Lahan dengan PT.HTJ) - Tesya Meidi; Harapan Tua RFS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of this study was to analyze and understand the performance of the Regional Financial and Asset Management Agency of Riau Province in providing data, especially on the settlement of land arrangements with PT.HTJ desire and to find out what factors hinder the performance of the organization. The background of this research is that there is a problem related to the management of land assets managed by the Regional Financial and Asset Management Agency and the unorganized land administration so that it affects the provision of data, especially on the settlement of land arrangements with PT.HTJ. For this reason, a performance measurement is required by the Regional Finance and Asset Management Agency which functions as an official for administering regional property in accordance with the Minister of Home Affairs Regulation No.19/2016. This study uses 6 (six) performance indivators by Mahsun (2014: 196) which consists of inputs, processes, outputs, outcomes, benefits and impacts. This type of research is qualitative research with a case study approach with data collection techniques including interviews, observation, and documentation. Based on the results of the research conducted, it can be concluded that the performance of the Regional Financial and Asset Management Agency in providing data, especially on the settlement of land arrangements with PT. Tata Jaya's passion is not optimal. This is caused by several inhibiting factors, namely weak administrative order and coordination. Keywords : Performance, Organization, Regional Assets